SCALE MORPHOLOGY OF THREE TELEOSTS (ETROPLUS SURATENSIS, ANABAS TESTUDINEUS, SARDINELLA LONGICEPS) WITH REFERENCE TO FUNCTION - Prakasam, V R; Johnson, Pius (Indian Journal of Fisheries, 2011)
Morphological study showed that the scales of Anabas testudineus are ctenoid, those of Sardinella longiceps are cycloid and both types of scales occur in Etroplus suratensis. In Anabas and Etroplus, the circuli are concentric in the submerged portion and they possess serrations, hitherto unreported, which may aid in anchoring the scale in its pocket. The circuli are discontinuous and tubular in the exposed portion of scales of Etroplus, whereas in Anabas they are not tubular but are uninterrupted by the formation of spines. In contrast, the circuli of Sardinella are either concentric or parallel, continuous or discontinuous and serrations are absent. In Etroplus and Anabas the radii are found only in the submerged areas. The radii, found in both exposed and submerged portions of Sardinella scales, are horizontal and transverse. They are also canal-like in certain scales. The average number of radii in Etroplus is 11.69 and it does not vary with increase in size of the fish, but in Anabas it is 23.42 and shows a linear rise with increase in total length of fish thereby making it possible to back-calculate the length of fish from the number of radii. It is suggested that radii may function in the capillary flow of water or mucus and that the ctenii may serve a defensive function. The nature of tubular circuli and canal like radii are described.